Breeding maize for broad-based resistance to striga hermonthica - Menkir, A.; Badu-Apraku, Baffour; Yallou, C.G.; Kamara, A.Y.; Ejeta, G. (World Scientific Publishing, 2007)
Recurrent selection under artificial S. hermonthica infestation has significantly reduced the number of emerged Striga plants and increased grain yield under Striga infestation in broad-based populations. These populations have been sources of varieties and inbred lines with consistently high levels of resistance to S. hermonthica across locations and seasons. The number of parasites attached to the roots of diverse lines was significantly correlated with the number of emerged parasites in the screenhouse and in the field as well as with a reduction in grain yield due to Striga. AFLP and SSR markers clearly separated 41 Striga resistant inbred lines from four populations into groups according to their source populations. The consistent ranking of the general combining ability effects of selected inbred lines across locations and seasons also indicates that the inbred lines had a stable genetic basis that controlled the Striga resistance traits. Unraveling the complex mechanisms of resistance to S. hermonthica using rapid and efficient screening tools can facilitate the improvement of maize for resistance to different populations of the parasite.